Comprehensive characterization and quantification of multiple components in Dan‐Huang‐Qu‐Yu capsule using a multivariate data processing approach based on microwave‐assisted extraction with UHPLC and Q Exactive quadrupole‐orbitrap high‐resolution mass spectrometry. Issue 11 (24th April 2019) - Yang, Bo; Ying, Yin; Zou, Jie; Ge, Shuyu; Zuo, Lihua
Abstract: Dan‐Huang‐Qu‐Yu capsule, a Chinese herbal medicine compound preparation, is widely used for chronic pelvic inflammatory disease. In this study, a rapid, selective, and sensitive microwave‐assisted extraction ultra‐high‐performance liquid chromatography‐Q Exactive quadrupole‐orbitrap high‐resolution mass spectrometry method was developed for analyzing its chemical compositions. A total of 85 compounds, including 22 flavonoids, 8 terpenoids, 5 quinones, 5 phthaleolactone, 23 organic acids, and 22 other compounds were identified from Dan‐Huang‐Qu‐Yu capsule. Among them, 35 major compounds were unambiguously detected by comparing them with reference standards and selected as quality control markers, which were simultaneously determined in Dan‐Huang‐Qu‐Yu capsule. The established method was successfully validated and applied for simultaneous determination of 35 bioactive compounds in Dan‐Huang‐Qu‐Yu capsule from ten sample batches. The quantitative data of the analytes were analyzed by principal component analysis for quality assessment of Dan‐Huang‐Qu‐Yu capsule. Six compounds (e.g., astragaloside IV, salvianolic acid B, ellagic acid, chlorogenic acid, N ‐butylidenephthalide, and luteolin) were screened out and regarded as chemical markers for quality control of Dan‐Huang‐Qu‐Yu capsule. The established method has been proved to be a novel and useful tool for rapid research of Dan‐Huang‐Qu‐Yu capsule. This research will provide reference for the scientific research of traditional Chinese medicines.